CRYPTOCURRENCY AND ITS DISRUPTIVE POTENTIAL: INVESTIGATING LONG-RUN AND SHORT-RUN RELATIONSHIPS WITH SOME SELECTED MACROECONOMIC INDICATORS - Ani, Chukwuemeka Lawrence; Afolabi, Abdulssamad Ayomide; Daramola, Deborah Abiola (FUDMA JOURNAL OF SCIENCES, 2025)
The advent of cryptocurrency and underlying blockchain technology has ushered in a new era of digital finance, challenging traditional economic frameworks and prompting a reassessment of the macroeconomic landscape. This research work delves into the multifaceted economic impact of cryptocurrency, examining its potential implications for monetary policy, financial stability, and economic growth. This study uses a time series approach, that is Johansen cointegration and Granger causality in determining both the long and short run relationship that exist between the exchange rate of cryptocurrency prices (Binance coin, Bitcoin, Dogecoin, Ethereum, And Ripple) versus the U.S dollar and GDP from January, 2018 to July, 2023. And While, it also focuses on checking the long run and short run equilibrium relationship between the economic/financial variables and cryptocurrency market capitalization from January, 2018 to July, 2023.  It considers a monthly data for both the exchange rates of the selected cryptocurrency prices versus the U.S dollar and the selected economic/financial time series variables. Finally, the study reveals that the result obtained from both tests. That is, the Johansen cointegration test and Granger causality Test, shows that short run effects exist more among the studied time series variables than in the long-run, and that changes in the selected cryptocurrency prices can be used to predict changes in the macroeconomic variables and indicators.
Keywords: Cryptocurrency; Macroeconomic indicators; Economic growth; Cointigeration; Granger causality